Enhancing Antimicrobial Peptide Productivity in Pichia pastoris (Muts Strain) by Improving the Fermentation Process Based on Increasing the Volumetric Methanol Consumption Rate - Chatchol Kongsinkaew; Supenya Chittapun; Chanitchote Piyapittayanun; Viroj Boonyaratanakornkit; Sarintip Sooksai; Kittisak Ajariyakhajorn; Soisuda Pornpukdeewattana; Warawut Krusong; Tunyaboon Laemthong; Theppanya Charoenrat (My University, 2023)
The instability of the protein expression in Pichia pastoris strains has been an issue for various peptide productions. Some modifications to the traditional fermentation process could potentially solve the problem. Here, we consider a four-stage fermentation process to express the CAP2 (cell-penetrating antimicrobial peptide 2) candidate in P. pastoris KM71H, a slow methanol utilization strain. During the fermentation process, CAP2 productivity is limited (6.15 ± 0.21 mg/L·h) by the low overall methanol consumption (approximately 645 g), which is mainly the result of the slow methanol utilization of the P. pastoris KM71H. To overcome this limitation, we increased the cell concentration two-fold prior to the induction stage. A fed-batch process with exponential and dissolved oxygen tension (DOT) stat feeding strategies was deployed to control the glycerol feed, resulting in an increase in cell concentration and enhancement of the volumetric methanol consumption rate. The improved fermentation process increased the overall methanol consumption (approximately 1070 g) and the CAP2 productivity (13.59 ± 0.24 mg/L·h) by 1.66 and 2.21 times, respectively. In addition, the CAP3 (cell-penetrating antimicrobial peptide 3) candidate could also be produced using this improved fermentation process at a high yield of 3.96 ± 0.02 g/L without any further optimization. Note that there was no oxygen limitation during the improved fermentation process operating at high cell density. This could be due to the controlled substrate addition via the DOT stat system.
Keywords: Antimicrobial Peptides and Activities